2020
DOI: 10.1111/aos.14357
|View full text |Cite
|
Sign up to set email alerts
|

An association of neovascular age‐related macular degeneration with polymorphisms of CFH, ARMS2, HTRA1 and C3 genes in Czech population

Abstract: PurposeWe investigated associations between neovascular age‐related macular degeneration (AMD) and rs10490924 polymorphism of ARMS2 gene (age‐related maculopathy susceptibility 2), rs1061170 polymorphism of gene for complement factor H (CFH), rs2230199 polymorphism of gene for complement component C3 and rs11200638 polymorphism of gene for serine protease high‐temperature requirement A1 (HTRA1) in the Czech population.MethodsWe analysed samples of DNA from 307 patients diagnosed with neovascular form of late A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
1
6
0
2
Order By: Relevance
“…People with the AA genotype had a 20-fold increased risk of having nAMD than those with the GG genotype. This finding is similar to results from other studies in other ethnic groups [ 12 , 17 19 , 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…People with the AA genotype had a 20-fold increased risk of having nAMD than those with the GG genotype. This finding is similar to results from other studies in other ethnic groups [ 12 , 17 19 , 22 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Patients with the AA genotype were more prone to have AMD by nearly 26-fold. The association remained strong after data adjustment with [12,[17][18][19][22][23][24].…”
Section: Discussionmentioning
confidence: 90%
“…This work represents progress toward personalized and precision medicine, although it has yet to be applied in clinical practice. No other study has yielded results of genetic determinants strongly associated with AMD risk [15,16]. Current data suggest that clinical characteristics, such as baseline best-corrected visual acuity (BCVA) and neovascularization lesion size, are superior to genetic findings for predicting AMD progression and making treatment decisions [11,17].…”
Section: Geneticsmentioning
confidence: 99%
“…Certain polymorphisms in ARMS2 and HTRA1 also are considered to confer risk of AMD [22]. Compared with control patients awaiting cataract surgery, patients with nAMD were significantly more likely to have certain polymorphisms in CFH (CC genotype), ARMS2 (TT), HTRA1 (AA), and C3 (CG), and these associations were stronger among women than among men [16]. Other investigators found that fewer than half of CFH variants were associated with AMD visual outcomes on anti-VEGF agents [19].…”
Section: Geneticsmentioning
confidence: 99%
“…[13][14][15]41 In contrast to ARMS2, associations between CFH Y402H gene variants and nAMD have been less consistent. 42 For example, CFH Y402H in Caucasian had a strong association with nAMD, 4,14,43,44 but studies from Asian showed a conflicting result. Xu et al, 34 Gotoh et al, 45 Okamoto et al, 46 Uka et al, 47 and Chen et al 48 showed a weak association of CFH Y402H with AMD while Lau et al 49 showed a contradictory result.…”
Section: Discussionmentioning
confidence: 99%